2010
DOI: 10.1051/0004-6361/200913386
|View full text |Cite
|
Sign up to set email alerts
|

Local simulations of the magnetized Kelvin-Helmholtz instability in neutron-star mergers

Abstract: Context. Global magnetohydrodynamic simulations show the growth of Kelvin-Helmholtz instabilities at the contact surface of two merging neutron stars. That region has been identified as the site of efficient amplification of magnetic fields. However, these global simulations, due to numerical limitations, were unable to determine the saturation level of the field strength, and thus the possible back-reaction of the magnetic field onto the flow. Aims. We investigate the amplification of initially weak magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 34 publications
2
97
0
Order By: Relevance
“…This weaker growth is also inconsistent with the amplification to local kinetic equipartition seen in small-scale simulations (Obergaulinger et al 2010;Zrake & MacFadyen 2013), and is attributed to insufficient resolution in the NS merger simulations (Giacomazzo et al 2014;Kiuchi et al 2014, though see Dionysopoulou et al 2015). Giacomazzo et al (2014) incorporated a subgrid magnetic amplification model, calibrated using Zrake & MacFadyen (2013)s results, into their Eulerian NS merger simulation, and found E B amplification by a factor of 10 10 ∼ over a single dynamical time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This weaker growth is also inconsistent with the amplification to local kinetic equipartition seen in small-scale simulations (Obergaulinger et al 2010;Zrake & MacFadyen 2013), and is attributed to insufficient resolution in the NS merger simulations (Giacomazzo et al 2014;Kiuchi et al 2014, though see Dionysopoulou et al 2015). Giacomazzo et al (2014) incorporated a subgrid magnetic amplification model, calibrated using Zrake & MacFadyen (2013)s results, into their Eulerian NS merger simulation, and found E B amplification by a factor of 10 10 ∼ over a single dynamical time.…”
Section: Discussionmentioning
confidence: 95%
“…Magnetohydrodynamic (MHD) double NS binary merger simulations (e.g., Price & Rosswog 2006;Giacomazzo et al 2014;Kiuchi et al 2014) have found that Kelvin-Helmholtz vortices produced along the shear interface between the coalescing stars can amplify field strengths by orders of magnitude (Obergaulinger et al 2010;Zrake & MacFadyen 2013). The same should hold true for WD mergers.…”
Section: Introductionmentioning
confidence: 96%
“…the exponential growth manifests itself as a linear slope [52][53][54] (see Fig.6). Therefore, γ can be obtained from the slope of a linear function fitted to the initial growth stage.…”
Section: A Linear Growth Rate and Velocity Gradient Effectmentioning
confidence: 99%
“…In the framework of sGRBs, the question of what field strengths could be reached in a merger remnant before it collapses to a BH has so far remained unanswered, neither evidence of magnetization in the jet has been found. Simulations have shown that during the merger the magnetic field strength can increase up to 10 16 G. The growth emerges from the transfer of hydrodynamical kinetic energy to electromagnetic energy via Kevin-Helmholtz instabilities and turbulent amplification (Price & Rosswog 2006;Zrake & MacFadyen 2013;Giacomazzo et al 2009;Obergaulinger et al 2010). The bright, short and hard GRB 090510 was detected by nifraija@astro.unam.mx, wlee@astro.unam.mx, pv0004@uah.edu and rbarniol@purdue.edu Fermi and Swift satellites (De Pasquale & et al 2010).…”
Section: Introductionmentioning
confidence: 99%